Hypogonadism and its associated factors among adult male type 2 diabetes mellitus patients at the university of gondar comprehensive specialized hospital, Northwest Ethiopia 2024: A comparative cross-sectional study - Arega Zenaw; Elias Chane; Getnet Fetene; Habtamu Wondifraw; Amare Mekuanint; Yonatan Kinde; Temesgen Kassie; Kassaw Demeke; Alebachew Fasil; Abebaw Worede (PLoS ONE, 2025)
Introduction Hypogonadism is an established complication in male patients with type 2 diabetes mellitus, potentially exacerbating metabolic dysregulation and impairing quality of life. Global studies have documented an elevated prevalence of hypogonadism among diabetic individuals. However, there remains a scarcity of data regarding the prevalence and contributing factors of hypogonadism in patients with type 2 diabetes mellitus in Ethiopia, particularly in the Gondar region. Methods and Materials This comparative cross-sectional study included 330 participants (165 with type 2 diabetes mellitus and 165 age-matched controls), selected via systematic random sampling from June 27 to August 20, 2024. Data were collected through structured questionnaires and 5 mL blood samples were obtained by laboratory technologist. Analysis using SPSS version 25 involved descriptive statistics, independent t-tests, and binary logistic regression to identify factors associated with hypogonadism, with significance set at p < 0.05. Result The mean age of participants was 57 ± 8.9 years in the type 2 diabetes mellitus (T2DM) group and 55 ± 8.6 years among controls. Hypogonadism was identified in 30.3% of individuals with T2DM, compared to 7.2% in the control group. Multivariable logistic regression revealed that T2DM, elevated fasting blood glucose, advancing age, dys-regulated high-density lipoprotein levels, and obesity were independently associated with increased odds of hypogonadism. Conclusion and Recommendation The prevalence of hypogonadism was markedly higher in individuals with type 2 diabetes mellitus compared to the control group, concomitant with a significantly lower mean testosterone level. Multivariate analyses identified fasting blood glucose, high-density lipoprotein levels, advanced age, the presence of diabetes, and obesity as independent risk factors for hypogonadism. Notably, modifiable factors such as obesity, in conjunction with key metabolic indicators, underscore potential targets for intervention to alleviate the burden of hypogonadism in diabetic patients.